Parodies of Ownership Hip-Hop Aesthetics and Intellectual Property Law - Schur, Richard (University of Michigan Press, 2011)
What is the relationship between hip-hop and African American culture in the post--Civil Rights era? Does hip-hop share a criticism of American culture or stand as an isolated and unique phenomenon? How have African American texts responded to the increasing role intellectual property law plays in regulating images, sounds, words, and logos? Parodies of Ownership examines how contemporary African American writers, artists, and musicians have developed an artistic form that Schur terms ""hip-hop aesthetics."" This book offers an in-depth examination of a wide range of contemporary African American painters and writers, including Anna Deavere Smith, Toni Morrison, Adrian Piper, Colson Whitehead, Michael Ray Charles, Alice Randall, and Fred Wilson. Their absence from conversations about African American culture has caused a misunderstanding about the nature of contemporary cultural issues and resulted in neglect of their innovative responses to the post--Civil Rights era. By considering their work as a cross-disciplinary and specifically African American cultural movement, Schur shows how a new paradigm for artistic creation has developed. Parodies of Ownership offers a broad analysis of post--Civil Rights era culture and provides the necessary context for understanding contemporary debates within American studies, African American studies, intellectual property law, African American literature, art history, and hip-hop studies. Weaving together law, literature, art, and music, Schur deftly clarifies the conceptual issues that unify contemporary African American culture, empowering this generation of artists, writers, and musicians to criticize how racism continues to affect our country.